Aves e mamíferos ameaçados de extinção em unidades de conservação: estudo de caso no Parque Nacional de Sete Cidades, Piauí - Campana, Lara Souza (2020)
Brazil is the 3rd richest country in avifauna in the world and the 2nd in mastofauna, it has about 1919 species of birds and 701 of mammals in its territory. The 234 taxa of birds officially considered threatened, the Cerrado and Caatinga have 34 taxa each and of the 102 continental mammals species the Cerrado has 41 and the Caatinga has 15. The present work carried out an ethno-zoo study with the threatened avifauna and mastofauna found in the Park Nacional de Sete Cidades (PNSC), Piauí, ecotone with both biomes. To identify the locally threatened taxa and the pressures suffered, semistructured interviews were conducted with staff and communities surrounding the PNSC, guided tours and the use of secondary data such as the official lists of threatened fauna (IUCN, ICMBio and CITES). Among the results, it was possible to verify that the threatened species are found in greater abundance within PARNA, according to the interviewees' perception. The birds of the family Cracidae (jacus) and Tinamidae (nambus) are the most threatened by subsistence and trade hunting and the Psittacidae, Emberizidae, Icteridae, Thraupidae and Turdidae families are the ones that suffer most from cage farming and illegal trafficking in the region. The mammals found in the PNSC considered most threatened are from the family Felidae, Dasypodidae, Drasypoctidae, Tayassuidae, Cervidae and Caviidae and the main threats found in the region are hunting and capture, deforestation, bushfires, roadkill and exotic species. As a final result, N = 29 bird species were found to be threatened locally and N = 22 species of mammals, serving as a guide for conservation actions in the region. Finally, it appears that PARNA Sete Cidades has viable and healthy habitats because it is a protected area, with priority areas to support the presence of some endemic species, dispersers, top predators and threatened species nationally and globally.